Penerapan Engineering Design Process dalam Pengembangan Tong Sampah Berbasis QR Code Terintegrasi Website untuk Pengelolaan Sampah Berbasis Masyarakat - Albertus Nyam Frandis; Rifaldi Herikson; Berta Erwin Slam; Rafi Dio (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Community-based waste management remains a challenge in residential environments, particularly due to low community participation in reporting waste bin conditions and the lack of information media for waste management activities. This condition highlights the need for technological innovation that can increase community involvement in waste management more effectively. This study aims to develop a technology-based innovation grounded in real community needs through the implementation of the Engineering Design Process (EDP). The research stages began with field observations to identify problems, followed by recording and grouping findings, formulating problems and solutions, creating initial sketches, comparing ideas with similar innovations, and selecting a solution in the form of a QR Code-based waste bin integrated with a website. Furthermore, a 3D design of the waste bin and a website interface were developed, followed by the construction of a simple prototype of the QR Code-based waste bin and a localhost-based website. The website provides features including a homepage, community profile, activity schedule, reporting, educational content, suggestion forms, and an admin page for data management. System testing was conducted through user testing involving community residents as system users. The results indicate that the majority of respondents considered the system easy to use, useful, and aligned with environmental needs, as reflected by positive feedback from all participants during interview-based testing. The study demonstrates that applying the Engineering Design Process through direct field observation can produce technological innovations that are relevant and provide tangible benefits for community-based waste management.